A comparative analysis of incremental and disruptive innovation policies in the european banking sector with hybrid interval type-2 fuzzy decision-making models - Dinçer, Hasan; Yüksel, Serhat; Martinez, Luis (Springer, 2020)
Nowadays innovation is a key issue in all business sectors, maintaining a positive correlation with the countries' economic development. The banking sector stands out among the different economic sectors, as globalization has pushed banks into tough competition. Hence, banks within this competitive framework must innovate by developing new products to be competitive and survive. The innovation in banking products is usually sorted as incremental or disruptive. Therefore, this paper aims to evaluate the innovation policies for the European Banking Sector by analyzing incremental and disruptive innovation policies. The novelty of the paper is to propose a set of dimensions and criteria for the innovation policies of European banking industry and to construct a hybrid decision-making model based on interval type-2 fuzzy sets. Accordingly, a comparative analysis of the top five GDP European countries has been carried out using a multiple criteria decision model (MCDM). The MCDM defines different criteria for incremental and disruptive innovations according to the specialized literature. Interval type-2 fuzzy DEMATEL (IT2 FDEMATEL) is used for weighting factors, and interval type-2 fuzzy VIKOR (IT2 FVIKOR) and interval type-2 fuzzy TOPSIS (IT2 FTOPSIS) are considered for ranking alternatives in the integrated modeling. Eventually, the findings highlight the most important criteria in this analysis and the results demonstrate that the comparative analysis of IT2 FVIKOR and IT2 FTOPSIS provides comprehensive and coherent results to select the best country in the innovation policies. In addition, the need to redesign the European banking system with necessary regulations to contribute to the development of the innovations is pointed out.
Keywords: Innovation; Europe; Banking Sector; Interval Type-2 Fuzzy DEMATEL; Interval Type-2 Fuzzy TOPSIS; Interval Type-2 Fuzzy VIKOR